Islam and democracy in Indonesia tolerance without liberalism - Menchik, Jeremy (Cambridge studies in social theory, religion and politics, 2016)
Indonesia's Islamic organizations sustain the country's thriving civil society, democracy, and reputation for tolerance amid diversity. Drawing on archival documents, ethnographic observation, comparative political theory, and an original survey, Islam and Democracy in Indonesia demonstrates that Indonesia's Muslim leaders favor a democracy in which individual rights and group-differentiated rights converge within a system of legal pluralism, a vision at odds with American-style secular government but common in Africa, Asia and Eastern Europe.